USING OF DYNAMIC AND STATIC LOAD PILING TESTS IN ASTANA, KAZAKHSTAN - Zhussupbekov, A. Z.; Shakhmov, Z. A.; Tleulenova, G. T.; Akhazhanov, S. B. (Academic journal Industrial Machine Building Civil Engineering, 2017)
In this paper the analysis results of precast piles different tests are presented. Extreme soil conditions of Astana (Kazakhstan) involve realizing the work precast piles in various soil ground and interaction soil ground and piles. There were carried out dynamic and static load tests of piles in extreme soil ground conditions in Astana. Based on data results of pile foundations the piles bearing capacity was determined. According to the results of DLT with PDA of driving piles (30.0 cm) the bearing capacity of the piles is 911 kN. The bearing capacity of the driven piles according to the results of SLT amounted to be 878 kN. Soils physic-mechanical properties in extreme conditions of Astana along with graphs of dependence are between settlement and load. The precise analysis of climatic and geological factors of the construction sites is shown. Investigations method for precast concrete piles testing is presented. Dynamic load test methodology in Astana for concrete piles testing is shown. These investigations are important for of Pile-Soil interaction on problematical soil ground.